Motor Responses and Weight Gaining in Neonates through Use of Two Methods of Earmuff and Receiving Silence in NICU - Z. Abdeyazdan; S. Ghasemi; M. Marofi; N. Berjis (The Scientific World Journal)
Background and Aims. With technological advances in NICUs the survival rate of preterm infants has been increased. Because NICU environment is a potent source of stress for infants, its modification is an essential measure to decrease infants’ morbidity. The purposes of this study were to compare the effects of wearing earmuff and provision silence for infants on their motor responses and gaining weight. Methods. In a randomized clinical trial 96 preterm infants were enrolled. Their motor responses were evaluated for two consecutive days in the morning and afternoon shifts, in the groups of earmuff and silence, and at similar time points in the control group. Also their weight was measured at days 1 and 10. Results. In the two intervention groups, means of motor responses in infants were significantly less than in the control group, and weight gain of infants was more than the control group. However weight gain was more pronounced in the earmuff group. Conclusion. Both interventions led to decreasing number of motor responses and improvement of weight gain pattern, but these effects were more pronounced in earmuff group; thus because implementation of silence in NICUs has many barriers, it is suggested to use earmuff for preterm infants in these units. This trial obtained IRCT registration number IRCT2012092010812N2.